Fungal communities in bunker C oil-impacted sites in Southern Guimaras, Philippines a post-spill assessment of Solar Oil I oil spill. - Sarinas, Brian Gil S. (University of the Philippines Visayas, 2010)
The results of rapid assessment of short term impacts on fungal population in oil-contaminated coastal habitats in 2006 in Southern Guimaras, Philippines showed disturbance on the mycoflora in terms of species composition and density. The present study was conducted after almost three years to determine if there is recovery or reinstatement of normal mycoflora in the same study sites. Specifically, it aimed to describe fungal population in terms of species composition and fungal load per site according to sample type, compare similairty of fungal population among sites and sample type, and quantify fungal density (CFU's per ml or g of sample). Samples were collected at the same eight sites in Guimaras : six oil-contaminated sites and two uncontaminated sites or referenced sites. Samples gathered were composed of beach water, beach soil, mangrove surface soil and mangrove sub-surface soil. Fungi were enumerated and isolated using the spread plate serial dilution technique and identified based on colony and microscopic chracters using available keys and monographs. In general, fungal density appeal to have increased over the three year period. There is also the dominance of the hyphomycetes similarto 2006 data, although not necessarily of the same species composition. The reduction of oil could have possibly caused a shift from oil-degrading species to the re-appearance of the normal mycoflora. Changes in fungal assemblages and density wee observed over the three-year period that could possibly be sigs of iniital recovery and re-establishment of normal fungal flora among the disturbed coastal habitats in Southern Guimaras, Philippines.